Pengaruh Disiplin Kerja, Motivasi Dan Kompetensi Terhadap Kinerja Karyawan Pada PT. Pelindo IV Cabang Makassar - rostini rostini; Muh Hasry Mukhtiali; Nurfatwa Andriani Yasin; Jumiati Nurdin (Economy Deposit Journal (E-DJ), 2022)
This study aims to determine the effect of work discipline, motivation and competence on employee performance at PT. Pelindo IV Makassar Branch. The method used is multiple regression analysis using a questionnaire. The sample in this study were employees of PT. Pelindo IV (Persero) Makassar Branch which was selected through the Census method with a total of 50 employees. The results of this study indicate that based on the partial test, the Work Discipline variable (X1) has a positive and significant effect on the Performance variable (Y), the Motivation variable (X2) has a positive and significant effect on the Performance variable (Y), and the Competence variable (X3) also has a positive effect. and significant to the Performance variable (Y). While the results of the simultaneous test of Work Discipline variable (X1), Motivation variable (X2) and Competence variable (X3) simultaneously have a positive and significant effect on Employee Performance (Y). The variable that has a more dominant influence is the competence variable.